THE INTERRELATIONSHIP BETWEEN REGIONAL SPECIALIZATION AND TOURISM DEVELOPMENT (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article provides a theoretical and practical analysis of the interrelationship between regional specialization and tourism development. The aim of the study is to identify the impact of territorial specialization on tourism development and to substantiate the mechanisms of integration between these processes. The research employs a systems approach, statistical analysis, comparative analysis, and territorial analysis methods.The findings indicate that the specialization of regions based on their natural, economic, and social resources constitutes an important factor in tourism development. At the same time, the development of tourism influences the economic structure of a region, deepening and diversifying its specialization. The study further substantiates that the institutional and economic capacity of territorial communities plays a significant role in tourism development.
Keywords: Regional specialization, tourism development, regional development, territorial community, economic system, tourism infrastructure, investment, sustainable development, regional economy, service sector, tourism potential, socio-economic efficiency, regional policy, local governance, recreational resources.